Bioetica giudiziaria in Italia: note critiche su una sentenza recente in tema di protezione della vita prenatale - Claudio Sartea (Universidad Hemisferios, 2014)
Inspired by a recent judgment of the Italian Court of Cassation, this paper presents a summary of the essential references of fact and law around the case, and offers some critical reflections on the topic, very conflictive, of the legal personality of the unborn. The reasoning inevitably turns toward the more general discourse concerning the foundation of individual rights, oscillating between liberty (voluntaristic and subjectivist outlook) and dignity (objectivist, and conditioned by the precautionary principle). On the basis of the preferred option, we will have a different conception of the role of biolaw in technologically advanced societies. After the presentation of the judicial case and the main legal arguments of the decision (first chapter), the article explores the crucial issue of legal personality of the unborn, from the dual perspective of law and philosophy of law, in particular justifying the equation that identifies human being and person (second chapter). Subsequently, the third chapter offers a reflection on the alternative between dignity and liberty in order to the foundation of individual rights, arguing the preference for a dignitary perspective: in fact, this defends better the vulnerable people and then really safeguards the equality. The last chapter before the conclusion connects the bioethical discussion with the consideration of task of biolaw and of the jurist in contemporary societies.